Performance of pre-breeding cycle-staging techniques in bitches: Clinical comparability of vaginal cytology and progesterone assay - Samuel Ayodele Famakinde; Oluropo Michael Obafemi; Tolulope Adeoye Ajayi; Olufisayo Oluwadamilare Leigh; Oreoluwa Raymond Akinbote; Adedamola O Olanrewaju; Deborah Boluwatife Ola; Oluwaseyi Oladiran Fakorede; Barakat Adedamola Salaudeen; Mutiat Busayo Rabiu (Ovozoa: Journal of Animal Reproduction, 2025)
Accurate timing of insemination (mating) remains a critical challenge in the reproductive management of bitches. In spite of technical advances in vaginal cytology (VC) and serum-progesterone (SP) assay, the challenges appeared not to have abated. Five clinical scenarios involving VC and SP are presented, aimed at investigating technique-performance and creating more robust awareness on application of SP titers obtained using a fluorescence immunoassay kit having 7.6–20.0 ng/mL as predictable-progesterone-titer-range-for-insemination-(PPTRi). Number of bitches, insemination-readiness-detection-technique(s) (IRDT), score (%) of agreement/disagreement between Insemination-readiness-detection techniques (SABT) for peculiarities of bred bitch(es) (PBB), proportion of bitches that became pregnant confirmed by relaxin assay and, number of pups littered were studied. Results obtained for number of bitches, IRDT, SABT or PBB, relaxin and number of pups littered, respectively were: 22, VC-SP, 81.8%/18.2%, 72.7% and, NA (i.e. not-available) (case I); 2, VC-SP, bitches mated after attaining PPTRi 10 and 13 days after been detected ready-for-mating via VC, 100%, and, 5 and 7, respectively (case II); 1, SP, bitch mated at SP of 4.401 ng/mL, 100% and, 11 (case III); 2, SP, first bitch mated at 4.682 ng/mL and the second at 7.049 ng/mL, 100% and, 9 and 12, respectively (case IV); 1, VC-SP, bitch mated once detected ready-for-mating by VC while SP at 24-hours post-mating was 2.852 ng/ mL, 100% and, 1 (case V). These findings suggest high-level agreement in accuracy of Insemination-readiness-detection between the two techniques, with none reflecting superiority. For better breeding successes, it is recommendable to inseminate earlier, during the peri-ovulation period.